Neonatal systemic candidiasis. Issue 4 (April 1985) - Smith, H; Congdon, P
Abstract : Ten babies who required neonatal intensive care developed systemic candidiasis. Eight were extremely preterm (28 weeks' gestation or less) and all received prolonged ventilation, multiple courses of broad spectrum antibiotics, and intravenous hyperalimentation. Diagnosis was established by culture of yeasts from suprapubic urine specimens; venous blood cultures proved unreliable. Initial treatment with 5-flucytosine alone in eight babies and combined with amphotericin B in two, eradicated the infection in nine babies, the treatment failure arising through diagnostic delay and development of resistance to 5-flucytosine. Prophylactic topical antifungal drugs, regular screening of suprapubic urine specimens, and prompt use of systemic antifungal agents before multifocal infection becomes established may reduce the incidence and improve outcome.